Un bianco geometrico: Lettura dall’Etica di Spinoza (Materiali di Estetica. Terza serie, 2023)
The article collects the speech given at the Spinoza Seminar at the Fondazione Corrente, on January 17th, 2023, by the contemporary Italian-Belgian artist Lorenzo Gatti (1955), who over the years has created a series of large ‘maps’ dedicated to Baruch Spinoza’s work Ethica, ordine geometrico demonstrata (1677).
Keywords: Contemporary art; Spinoza; Art and philosophy